Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00213-013-3372-6
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol craving in adolescents: bridging the laboratory and natural environment

Abstract: Rationale Initial lab studies suggest that adolescent drinkers crave alcohol when presented with alcohol cues. Whether this effect generalizes to the natural environment, however, remains unknown, and studies have not examined whether craving predicts drinking among youths. Objectives This study builds on existing research by pairing controlled lab-based cue reactivity assessments with data collected in the natural environment using ecological momentary assessment (EMA) methods. We examined whether alcohol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 37 publications
(45 reference statements)
4
76
1
Order By: Relevance
“…That is, exposure to alcohol cues increased attentional bias towards the alcohol stimuli in the visual probe task for both Groups SE and LE. This finding is consistent with past work in which increases in attentional bias were observed following manipulations that increase craving (Cox et al, 1999; Ramirez et al, 2014). It is also noteworthy that the current effects of alcohol cue exposure on attentional bias occurred in a sample of UCSDs that reported relatively low mean rates of alcohol consumption and related problems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That is, exposure to alcohol cues increased attentional bias towards the alcohol stimuli in the visual probe task for both Groups SE and LE. This finding is consistent with past work in which increases in attentional bias were observed following manipulations that increase craving (Cox et al, 1999; Ramirez et al, 2014). It is also noteworthy that the current effects of alcohol cue exposure on attentional bias occurred in a sample of UCSDs that reported relatively low mean rates of alcohol consumption and related problems.…”
Section: Discussionsupporting
confidence: 92%
“…Future research will need to include manipulations that successfully reduce subjective reports of craving to determine whether reductions in craving are associated with reductions in attentional bias. Although other studies have demonstrated simultaneous reductions in craving and attentional bias for alcohol (Rose et al, 2013; Taylor et al, 2013), nicotine (Oh & Taylor, 2014; Szasz et al, 2012; Van Rensburg et al, 2009) and food (Oh & Taylor, 2013; 2014), current evidence to support a positive relationship between alcohol craving and attentional bias for alcohol is limited to studies that report reciprocal increases in these constructs (Ramirez et al, 2014). …”
Section: Discussionmentioning
confidence: 95%
“…With the advent of smartphones, researchers have, increasingly, been programming study-specific applications (apps) for use in such studies. In most cases, this involves either providing participants with a phone preloaded with the app [12,13], or loading the app onto participants' own phones and downloading the data at end of the experimental period [14].…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of these mechanisms to adolescent substance misuse, however, is largely speculative. For example, the relevance of craving, a major focus of adult research, to adolescent substance misuse was, until recently, largely under studied (77). Moreover, even with evidence that adolescents experience craving, questions remain about its relevance to addiction in this age group (77).…”
Section: Introductionmentioning
confidence: 99%
“…Momentary assessments are particularly important when the phenomena of interest are subject to rapid change, as are substance use, craving, and the acute subjective effects of alcohol and other drugs. We (and many others) have used this approach to study precursors and consequences of drinking alcohol (i.e., mood, cognitions) with adult and adolescent social and heavy drinkers, as well as patterns and effects of nicotine use with heavy smokers (77, 81-91). Notably, studies show that self-monitoring using EMA has little or no effect on drug use (92, 93).…”
Section: Introductionmentioning
confidence: 99%